Multicultural Counseling in the 21st Century: Redefining Professional Services in the Era of Globalization - Eric Komba Foyoh Mani; Martha Fanta Mansaray (International Journal of Counseling and Psychotherapy, 2025)
Background: Multicultural understanding in counseling services is essential to ensure that counselors respect and assess the cultural background of counselees without bias or discrimination, making it necessary to integrate multicultural values into every counseling interaction. Objective: This study aims to explore the urgency of multicultural counseling as a new paradigm in 21st-century counseling practices. Method: Using the Systematic Literature Review (SLR) method, this study systematically examines relevant national and international literature to analyze the theoretical foundations, dimensions, and practical implications of multicultural counseling. Result: The findings highlight seven key thematic areas: culture in the context of counseling, multicultural counseling paradigms, cultural dimensions in counseling interactions, multicultural counseling competencies, multicultural counseling approaches, counseling models, and emerging perspectives of multicultural counseling in the 21st century. The discussion emphasizes that multicultural counseling enhances counselor effectiveness by fostering cultural sensitivity, ethical awareness, and adaptive intervention strategies in diverse cultural settings. Conclusion: The study concludes that multicultural counseling is an essential component in developing inclusive guidance and counseling services. Contribution: This study contributes to the strengthening of the theoretical development in multicultural counseling and provides practical implications for enhancing counselor competence in diverse educational and social environments.